Effects of racquets on the development of tennis elbow injury - Shadgan, B. (2002)
Lateral epicondylitis, or tennis elbow, is one of the most common injuries in athletes, especially in racket players. This injury occurs almost exclusively as a result of repetitive overload. Pathologic change is seen in the extensor tendon attachments around the lateral epicondyle, especially in the extensor carpi radialis brevis. Studying the ways to prevent tennis elbow is useful, because once the injury is established, treatment can be a prolonged and complicated process. In a part of our retrospective and prospective study, 248 male tennis players at a private tennis club in Tehran were kept under the close observation of medical and technical teams for sports injuries between 1995 and 2000. All the subjects were non-professional club members with a minimum two hours practice per week for at least one year, in addition to a minimum six months of follow-up. Tennis players with tennis elbow injury were compared to the other players. The players were followed for an average of 38 months (range: six to 54 months). 42% of the players experienced tennis elbow at least once during their playing history, or had a recurrence during the study period. The average age of the subjects was 36, with a range from 17 to 68. 74% had other muscle-skeletal problems, mainly involving the shoulders. A significantly higher percentage of involvement was found in right-handed than in left-handed players. In the main part of the survey, researchers tried to identify the influence of racquet characteristics on the incidence of tennis elbow. The results of data analyses revealed the aggravating effects of racquet characteristics such as rigidity, heavy weights, heavy heads, long bodies, small head size, small and short handle grip size, and high string tension. Some other variables were also taken into consideration. The outcomes of a literature review and comparison of the results led to conclusions and recommendations on a number of preventive considerations.